Control Balance, Personality Traits, Attachment, and Communication Styles Associated with Stalking - Sciarrotta, Danika R. (Journal of interpersonal violence, 2022)
Stalking is associated with negative occupational, physical, social, and psychological consequences, yet little is known about who is at risk of being stalked. The purpose of the current study was to determine if individuals with experiences of being stalked have unique personality traits, attachment, and communication styles. Participants (N = 180; 78% female, mean age = 24, SD = 8.18) completed an online, self-report survey utilizing a cross-sectional, correlational design. Results indicated that 21% (N = 38) of participants reported experiences of being stalked. Those who had experienced stalking had a higher control deficit (t = 3.99, p = .000), higher control surplus (t = 2.14, p = .03), and lower general health scores (t = ?2.50, p = .01), as compared to participants who had not experienced stalking. Results also showed that those who had experienced stalking possessed higher scores of openness (F = 5.41, p = .021), neuroticism (F = 5.29, p = .023), and motivation to defer to a dominant partner (F = 46.79, p = .000). A logistic regression revealed that higher scores on neuroticism, motivation to defer to a dominant partner, and extroversion were associated with an increased risk of being stalked, whereas higher scores on interpersonal deference, disequilibrium, and agreeableness decreased college students? risk of being stalked (?2 (11, N = 180) = 67.34, p < .001). Findings provide information that may be used to decrease the prevalence of stalking victimization and inform clinical treatment for victims of this crime.